Determinants of Financing Disbursed by Islamic Rural Banks (BPRS) in Indonesia - Khairatun Hisan; Riski Syahpitri; Zulkarnaini Zulkarnaini (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This study aims to determine the factors influencing the total financing disbursed (PYD) in Islamic Rural Banks in Indonesia in the 2015-2019 period. The data in this study were collected from the documentation on the Financial Services Authority (OJK) official website from a quarter I 2015 to quarter IV 2019. The data were analyzed using the multiple regression method with SPSS software. The results showed that Third Party Funds (Dana Pihak Ketiga) positively and significantly affected the total disbursed financing (p-value 0.000). Non-Performing Financing (NPF) has a positive and significant effect on total financing (p-value 0.004). Return on Assets (ROA) has a positive and significant effect on total financing (p-value 0.035). Simultaneously, the three variables also positively affect the total financing disbursed by Islamic Rural Banks in Indonesia (p-value 0.000) with an Adjusted R Square value of 0.968 or 96.8%. The findings of this study contribute to the development of empirical studies related to the determinants of financing in microfinance institutions such as Islamic Rural Banks and can be used as a reference for financing management in Islamic Rural Banks.Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi total pembiayaan yang disalurkan (PYD) pada BPRS di Indonesia dalam periode 2015-2019. Data dalam penelitian ini dikumpulkan dari dokumentasi website resmi Otoritas Jasa Keuangan dari triwulan I 2015 - triwulan IV 2019. Data dianalisis dengan menggunakan metode regresi berganda dengan software SPSS 16.0. Hasil penelitian menunjukkan bahwa Dana Pihak Ketiga (DPK) berpengaruh positif dan signifikan terhadap total pembiayaan disalurkan (p-value 0,000). Non Performing Financing (NPF) berpengaruh positif dan signifikan terhadap total pembiayaan (p-value 0,004). Return on Asset (ROA) berpengaruh positif dan signifikan terhadap total pembiayaan (p-value 0,035). Secara simultan ketiga variabel juga berpengaruh positif dan signifikan terhadap total pembiayaan yang diberikan BPRS di Indonesia (p-value 0,000) dengan nilai Adjusted R Square sebesar 0,968 atau 96,8%. Temuan penelitian ini berkontribusi dalam pengembangan studi-studi empiris terkait determinan pembiayaan pada lembaga keuangan mikro seperti BPRS dan dapat digunakan untuk acuan pengelolaan pembiayaan di BPRS.